Implementation of the Inquiry Learning Model Integrated Ethno-STEM for Secondary Metabolites on the Concept Mastery and Conservation Characteristics of Students - Sudarmin Sudarmin; Rr. Sri Endang Pujiastuti; Skunda Diliarosta; Ariyatun Ariyatun; Rehani Ramadhani (Universitas Negeri Semarang, 2022)
The purpose of this research is to determine the effect of the Implementation of the Inquiry Learning Model Integrated Ethno-STEM for Secondary Metabolites on the Concept Mastery and Conservation Characteristics of Students. This research is part of the Basic Research of Higher Education Excellence in 2022. The research begins in 2021 by (1) developing an ethno-STEM integrated inquiry learning model with the Sudarmin syntax through the define, design, and development stages, (2) the preparation of research instruments for mastering chemical concepts organic and conservation characters which are further validated. In this research, the application of an evaluation tool for mastery of conservation concepts and characters assisted by the google form application after learning with the Ethno-STEM integrated inquiry learning model that has been produced. The research subjects are students of chemistry education at the Faculty of Mathematics and Science (FMIPA) of Universitas Negeri Semarang for the 2021/2022 academic year. At the end of the implementation of the Ethno-STEM Integrated Inquiry learning model with the Sudarmin syntax the data were analyzed. The results of the research concluded (a) Students' concept mastery scores still need to be improved, because based on N-gain scores there are still many moderate categories, (b) understanding of the conservation character of students regarding secondary metabolites from Indonesian tropical forest plants and their benefits in achieving good categories, (c) ) The overall results of the learning activities show a positive response to the model that has been developed.